Ministry with Persons with Mental Illness and Their Families, Second Edition - Thurber, Steven D.; Meller, William; Albers, Robert H. (Book collections on Project MUSE., 2019)
Those who are afflicted as well as those who are adversely affected by mental illness often live lives of "quiet desperation" without recourse to appropriate assistance. Most caregivers confronted with these illnesses in the work of ministry have had no training or accurate information about mental illnesses, so frequently they do nothing, resulting in further harm and damage. Others may operate out of a theological system that does not adequately account for the nature, severity, or treatment of these illnesses. In Ministry with Persons with Mental Illness and Their Families, Second Edition, psychiatrists and pastoral theologians come together in an interdisciplinary, collaborative effort to ensure accuracy of information concerning the medical dimensions of mental illness, interpret these illnesses from a faith perspective, and make suggestions relative to effective ministry. Readers will learn how science and a faith tradition can not only co-exist but work in tandem to alleviate the pain of the afflicted and affected.